Under-five mortality pattern and associated risk factors: a case-control study at the Princess Marie Louise Children's Hospital in Accra, Ghana. Issue 1 (December 2016) - Tette, Edem; Nyarko, Mame; Nartey, Edmund; Neizer, Margaret; Egbefome, Adolph; Akosa, Fredua; Biritwum, Richard
Abstract Background Millions of children under the age of 5 years die every year. Some of these deaths occur in hospitals and are related to both clinical characteristics and modifiable risk factors. This study investigates the association between malnutrition and mortality and profiles the presenting features in a case-control study of children under 5 years of age who attended Princess Marie Louise Children's Hospital (PML) in 2011. Methods A total of 120 cases of children under the age of 5 years who were admitted to hospital and died there were matched by sex and age to 120 controls who were children who survived on 1:1 basis from a record of patients admitted to PML in 2011. Data on socio-demographic and clinical characteristics were extracted from the medical records of the study participants. The association between malnutrition and mortality was determined by conditional logistic regression reported as odds ratios (OR) and their 95 % confidence interval (95 % CI).P  < 0.05 was considered significant in all analyses. Results Malnutrition was significantly associated with mortality in children under-5 years of age attending PML. In the adjusted analysis, the odds of dying was significantly higher in malnourished children compared with well-nourished children (adjusted OR = 4.32 [95 % CI, 1.33–13.92], p  = 0.014]). In addition, a previous episode of diarrhoea within the last year was associated with mortality (adjusted OR = 7.25 [95 % CI, 1.68–31.22], p  = 0.008). The proportion of patients with noisy or difficulty breathing, pallor, lethargic appearance, ill-looking appearance, febrile convulsion, altered sensorium, skin lesions, hepatomegaly or oedema was significantly higher among cases than in controls (p  < 0.05). Conclusions Malnutrition and a previous episode of diarrhoea within the last year were the main risk factors for mortality. Efforts to prevent malnutrition and diarrhoea must be intensified and a protocol to follow-up diarrhoea patients may be beneficial. Six out of the nine clinical features that were proportionally higher in children who died than those who survived, are captured by the Emergency Triage Assessment and Treatment (ETAT) screening protocol as emergency or priority signs, giving credence to the use of ETAT in this setting. Thus education of health professionals on the use of the tool to triage patients should be on-going. However, further studies are needed to establish whether the other clinical signs are consistently associated with mortality and if so, whether they can be included among triage criteria, danger signs or in a prognostic scoring system for this setting.